Thioredoxin-1 Attenuates Ventricular and Mitochondrial Postischemic Dysfunction in the Stunned Myocardium of Transgenic Mice - Perez, María Virginia (2016)
Aim: We evaluated the effect of thioredoxin1 (Trx1) system on postischemic ventricular and mitochondrial dysfunction using transgenic mice overexpressing cardiac Trx1 and a dominant negative (DN-Trx1) mutant (C32S/C35S) of Trx1. Langendorff-perfused hearts were subjected to 15 min of ischemia followed by 30 min of reperfusion (R). We measured left ventricular developed pressure (LVDP, mmHg), left ventricular end diastolic pressure (LVEDP, mmHg), and t63 (relaxation index, msec). Mitochondrial respiration, SERCA2a, phospholamban (PLB), and phospholamban phosphorylation (p-PLB) Thr17 expression (Western blot) were also evaluated. Results: At 30 min of reperfusion, Trx1 improved contractile state (LVDP: Trx1: 57.4 ± 4.9 vs. Wt: 27.1 ± 6.3 and DN-Trx1: 29.2 ± 7.1, p < 0.05); decreased myocardial stiffness (LVEDP: Wt: 24.5 ± 4.8 vs. Trx1: 11.8 ± 2.9, p < 0.05); and improved the isovolumic relaxation (t63: Wt: 63.3 ± 3.2 vs. Trx1: 51.4 ± 1.9, p < 0.05). DN-Trx1 mice aggravated the myocardial stiffness and isovolumic relaxation. Only the expression of p-PLB Thr17 increased at 1.5 min R in Wt and DN-Trx1 groups. At 30 min of reperfusion, state 3 mitochondrial O2 consumption was impaired by 13% in Wt and by 33% in DN-Trx1. ADP/O ratios for Wt and DN-Trx1 decrease by 25% and 28%, respectively; whereas the Trx1 does not change after ischemia and reperfusion (I/R). Interestingly, baseline values of complex I activity were increased in Trx1 mice; they were 24% and 47% higher than in Wt and DN-Trx1 mice, respectively (p < 0.01). Innovation and Conclusion: These results strongly suggest that Trx1 ameliorates the myocardial effects of I/R by improving the free radical-mediated damage in cardiac and mitochondrial function, opening the possibility of new therapeutic strategies in coronary artery disease.